Swing leg kinetics of human maximal accelerated sprinting - Nagahara, R.; Matsubayashi, T.; Matsuo, A.; Zushi, K. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Accelerated sprinting is one of the important abilities for athletes in many sports. This study aimed to investigate the step-tostep changes in kinetics of swing leg during the entire acceleration phase of maximal sprinting. Methods: Twelve male sprinters ran 60-m with maximal effort, during which three dimensional kinematics of the sprinters for 50 m from starting line were obtained. Based on the cordinate data, swing leg joint torque and power at each stride were calculated. Results: Peak hip extension and flexion torques during the swing phase increased rapidly with increasing running speed up to the 5th or 6th step (ca. 5.0 and 5.1 Nm/kg) and leveled off thereafter when the running speed still increased toward maximal running speed (10.1 m/s) which appeared at the 23rd step. Peak knee extension torque during the swing phase slightly increased step to step through the entire acceleration phase, while peak knee flexion torque during the swing phase increased acutely until the 8th step and then the tendency of increase became small (maximum values were 0.8 and 2.3 Nm/kg). In regard to joint torque power, positive and negative peaks at the hip in the sagittal plane increased to the 7th or 8th step (ca. 2.8 and 3.1 kW/kg) and the magnitudes were subsequently maintained. On the other hand, for the knee joint torque power, positive and negative peaks in the sagittal plane increased during the entire acceleration phase (maximum values were 0.7 and 2.6 kW/kg). Discussion: Although running speed increased rapidly and then did gradually during the entire acceleration phase, peak hip extension and flexion torques and positive and negative powers in the sagittal plane roughly reached the maximum values at the early stage of the acceleration. Nagahara et al. (in press) have recently verified that there are three sections which are delimited at the 4th and 16th step during the entire acceleration phase. Moreover, they speculated that the different acceleration strategies are needed during the respective acceleration sections. The characteristics of changes in kinetics during maximal accelerated sprinting in the present study support their speculation. Moreover, it seems that the force productions at the hip in the sagittal plane during the swing phase assume a large role in acceleration during the early stage of acceleration phase and those at the knee contribute for further increase in speed during the latter stage of the entire acceleration phase.